A Review on the Criteria of Evaluating the Reliability of Persian Manuscripts - Mojtaba Mojarrad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Historical and literary texts pass various stages from the moment of collecting manuscripts to publishing. In this process, the most important and influential step is a textual criticism. In this critique, first, the manuscripts are evaluated. This evaluation is the basic foundation of textual criticism, if scientific and accurate methods are taken into account, , the results will be presented more accurately and reliably. In this article, the criteria to evaluate the reliability of Persian manuscripts have been recognized, and according to scribes, corroborants, date of calligraphy, genealogy, and stylistics have been divided into five main groups, and each one of these criteria has been studied, recognized, and reviewed. After reviewing the criteria, it has been shown that none of these criteria can be the only criterion toevaluate the reliability, and the best way for evaluating the manuscripts is using a combination of two or more criteria based on the quantity and quality of manuscripts.